Exploring the behavioural approach for sustainable tourism - Nunes, Celso Pereira (2020)
The behavioural approach to sustainable tourism has received considerable attention and interest from the academic community within various fields of study. It has particular value for developing sustainable social practices. In this article, we investigate the contributions of the behavioural approach in the economic sciences, psychology, and adult education. Our objective is to reinforce the notion that individuals have the capacity to alter their behaviour to achieve active participation in unity with nature that firmly favours both their own wellbeing and environmental protection. We distinguish the term tourism as not only as a leisure activity, but also as a turning or changing point (while individuals adapt their performance in tune with nature to find the ways to achieve physical, mental, and spiritual equilibrium. Thereby, we make a further step to discussions on how exploration of the behavioural approach can support initiatives that promote environmental protection, and innovative tourism education programmes.